2023
DOI: 10.3389/fmicb.2023.1251275
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Lactiplantibacillus plantarum regulating Ca2+ affecting the replication of PEDV in small intestinal epithelial cells

Zifei Kan,
Shujuan Zhang,
Guisong Liao
et al.

Abstract: Porcine epidemic diarrhea virus (PEDV) mainly invades the small intestine and promotes an inflammatory response, eventually leading to severe diarrhea, vomiting, dehydration, and even death of piglets, which seriously threatens the economic development of pig farming. In recent years, researchers have found that probiotics can improve the intestinal microenvironment and reduce diarrhea. At the same time, certain probiotics have been shown to have antiviral effects; however, their mechanisms are different. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Calcium plays a key role in many bio-homeostasis functions. Previous results showed that PEDV infection causes a significant difference in the intra- and extracellular Ca 2+ concentrations, PEDV infection causes a significant increase in the flow of Ca 2+ from the extracellular space into the cells ( Kan et al, 2023 ). In this study, serum CA content in PEDV group decreased, which was consistent with the results of TRPV6 in subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium plays a key role in many bio-homeostasis functions. Previous results showed that PEDV infection causes a significant difference in the intra- and extracellular Ca 2+ concentrations, PEDV infection causes a significant increase in the flow of Ca 2+ from the extracellular space into the cells ( Kan et al, 2023 ). In this study, serum CA content in PEDV group decreased, which was consistent with the results of TRPV6 in subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%